Analisis Kebutuhan Anak Usia Dasar dan Implikasinya dalam Penyelenggara Pendidikan - Annisa Nidaur Rohmah; Amar, Abu (IBTIDA', 2020)
Every stage of human development process has unequal needs at each level. Same as stage of children of basic age, adolescence, adulthood and old age. In children aged 6-12 years , the needs that must be complied depend on other people (parents, siblings, teacher, friends, etc because they have not been able to comply their needs personally. This study aims to analyze the needs of basic children’s age and their implications for applaying of education. The research method used is a qualitative research method of library research. Based on the result of the analysis of the needs of basic children’s age covering several aspects, yhe most important thing is that parents and teachers must understand the level of needs of basic children’s age because this is closely related to the educational process of the child it self.